Spontaneous and experimental poisoning by Eupatorium tremulum (Asteraceae) in cattle Intoxicação espontânea e experimental por Eupatorium tremulum (Asteraceae) em bovinos - Lucioli J.* (2007)
The spontaneous and experimental poisoning by Eupatorium tremulum in cattle is described. Spontaneous cases were diagnosed in a herd of 19 cattle in the municipality of Lages, Santa Catarina, Brazil. Three of the animals were found dead after having been transferred to a pasture with abundant quantities of E. tremulum. On two of them postmortem examination was performed and several internal organs were sampled for histological examination. Green leaves of E. tremulum were force-fed orally to 5 calves in single doses of 23-32g/kg body weight. Three calves showed clinical signs and two died. The main clinical signs included anorexia, apathy, absence of rumen movements, diarrhea and a flabby abdominal wall. Gross changes were restricted to the fore stomachs and were identical to those observed in the cases of natural poisoning. Rumen and reticulum were slightly reddish from outside; the corneal layer of their internal lining was loosely attached to a markedly red mucosa. The histological examination of rumen and reticulum from spontaneous and experimental cases revealed necrosis and vesicle formation in the epithelium; in some segments of the ruminal mucosa there was detachment of the epithelial covering and infiltration by neuthophils. Poisoning by E. tremulum has clinical course, gross lesions and histopathology very similar to those observed in poisoning caused by ingestion of the plants Baccharidastrum triplinervium, Baccharis coridifolia and Baccharis megapotamica var. weirii. The diagnosis of the spontaneous cases here described was confirmed by epidemiological data and the experimental reproduction of characteristic gross lesions and histopathology.